Nano Ni layered anode for enhanced MCFC performance at reduced operating temperature - Hoang Viet Phuc Nguyen; Othman, Mohd Roslee; Seo, Dongho; Yoon, Sung Pil; Ham, Hyung Chul; Nam, Suk Woo; Han, Jonghee; Kim, Jinsoo (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
Nanoparticles of Ni and Ni-Al2O3 were coated on a molten carbonate fuel cell (MCFC) anode by spray method to enlarge the electrochemical reaction sites at triple phase boundaries (TPBs). Both nano Ni coated anode and nano Ni-Al2O3 anode exhibited significant reduction of anode polarization, thanks to smaller charge transfer resistance. The maximum power density of nano Ni coated anode was 159 mW cm(-2) at current density of 300 mA cm(-2) operating at 600 degrees C. This is about 7% increase from the standard cell performance tested and compared in the study. Although low performance of nano coated Ni-Al2O3 cell is observed due to electrolyte consumption, the stability of cell performance during operation time is more favorable in MCFCs operation. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: CARBONATE FUEL-CELLS; FABRICATION; ELECTRODES; CATHODE